Modulation of cardiac connexin-43 by omega-3 fatty acid ethyl-ester supplementation demonstrated in spontaneously diabetic rats - Radosinska, J; Kurahara, L H; Hiraishi, K; Viczenczova, C; Egan Benova, T; Szeiffova Bacova, B; Dosenko, V; Navarova, J; Obsitnik, B; Imanaga, I; Soukup, T; Tribulova, N (Physiological research, 2015)
Previous data suggest that type 1 diabetes mellitus leads to the deterioration of myocardial intercellular communication mediated by connexin-43 (Cx43) channels. We therefore aimed to explore Cx43, PKC signaling and ultrastructure in non-treated and omega-3 fatty acid (omega-3) treated spontaneously diabetic Goto-Kakizaki (GK) rats considered as type 2 diabetes model. Four-week-old GK and non-diabetic Wistar-Clea rats were fed omega-3 (200 mg/kg/day) for 2 months and compared with untreated rats. Real-time PCR and immunoblotting were performed to determine Cx43, PKC-epsilon and PKC-delta expression. In situ Cx43 was examined by immunohistochemistry and subcellular alterations by electron microscopy. Omega-3 intake reduced blood glucose, triglycerides, and cholesterol in diabetic rats and this was associated with improved integrity of cardiomyocytes and capillaries in the heart. Myocardial Cx43 mRNA and protein levels were higher in diabetic versus non-diabetic rats and were further enhanced by omega-3. The ratio of phosphorylated (functional) to non-phosphorylated Cx43 was lower in diabetic compared to non-diabetic rats but was increased by omega-3, in part due to up-regulation of PKC-epsilon. In addition, pro-apoptotic PKC-delta expression was decreased. In conclusion, spontaneously diabetic rats at an early stage of disease benefit from omega-3 intake due to its hypoglycemic effect, upregulation of myocardial Cx43, and preservation of cardiovascular ultrastructure. These findings indicates that supplementation of omega-3 may be beneficial also in the management of diabetes in humans.
Keywords: Animals; Heart; experimentální diabetes mellitus; fixní kombinace léků; kyseliny dokosahexaenové; Dietary Supplements; kyselina eikosapentaenová; srdce; Eicosapentaenoic Acid; potravní doplňky; Drug Evaluation, Preclinical; proteinkinasa C-epsilon; preklinické hodnocení léčiv; Male; Drug Combinations; Connexin 43; krysa rodu Rattus; konexin 43; zvířata; mužské pohlaví; Protein Kinase C-epsilon; Myocardium; Protein Kinase C-delta; myokard; Rats; proteinkinasa C-delta; Docosahexaenoic Acids; Diabetes Mellitus, Experimental